Studies on the subfamily Exothecinae (Hymenoptera: Braconidae) with the description of a new genus and a new species from India - Singh, Longjam Roni Kumar; Achterberg, C. Van; Sheela, S. (Zootaxa, 2022)
A new genus of the subfamily Exothecinae, Occipitotus Singh & van Achterberg gen. nov. is proposed. The type species Occipitotus langpramensis Singh & van Achterberg sp. nov., is described and illustrated, which is the second species of the subfamily known from India. A key to the extant genera of the subfamily Exothecinae is provided.